Molecular Basis of Modulating Adenosine Receptors Activities - Mahmod Al-Qattan, Mohammed N.; Mordi, Mohd Nizam (Current Pharmaceutical Design, 2019)
Modulating cellular processes through extracellular chemical stimuli is medicinally an attractive approach to control disease conditions. GPCRs are the most important group of transmembranal receptors that produce different patterns of activations using intracellular mediators (such as G-proteins and Beta-arrestins). Adenosine receptors (ARs) belong to GPCR class and are divided into A1AR, A2AAR, A2BAR and A3AR. ARs control different physiological activities thus considered valuable target to control neural, heart, inflammatory and other metabolic disorders. Targeting ARs using small molecules essentially works by binding orthosteric and/or allosteric sites of the receptors. Although targeting orthosteric site is considered typical to modulate receptor activity, allosteric sites provide better subtype selectivity, saturable modulation of activity and variable activation patterns. Each receptor exists in dynamical equilibrium between conformational ensembles. The equilibrium is affected by receptor interaction with other molecules. Changing the population of conformational ensembles of the receptor is the method by which orthosteric, allosteric and other cellular components control receptor signaling. Herein, the interactions of ARs with orthosteric, allosteric ligands as well as intracellular mediators are described. A quinary interaction model for the receptor is proposed and energy wells for major conformational ensembles are retrieved.
Keywords: interaction model